Innowacje a rozwój turystyki na obszarach wiejskich - Woźniak, Marian; Lechwar, Małgorzata (Innovations and Development of Tourism on Rural Areas, 2006)
The article raises the issue of innovation of rural areas in a diversified economy of a village. The village, which at the beggining of the third millenium is not only equated with agriculture and food providing, is to a large degree perceived in ecological-tourist-recreational character. Taking it into consideration more attention should be focused on a tourist offer of a Polish village and a new look at rural tourist product.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 672-678